D5.4 – International Network (RS and CH) web-site - Hadjimitsis, Diofantos G.; Lysandrou, Vasiliki; Themistocleous, Kyriacos; Tzouvaras, Marios; Agapiou, Athos; Christofe, Andreas; Nisantzi, Argyro; Mettas, Christodoulos; Evagorou, Evagoras G.; Papoutsa, Christiana; Lasaponara, Rosa; Masini, Nicola; et al. (My University, 2018)
The present deliverable makes part of the Work Package 5: Promotion of the centre locally and internationally, and more specifically it adress the International networking achieved through the website of the project.
Keywords: ATHENA project; Website